Features of Emotional and Volitional Stability of Police Officers at Various Stages of Occupational Genesis - Goncharova, N.A.; Dushkin, A.S.; Konopleva, I.N.; Pryakhina, M.V. (Psihologiâ i pravo, 2023)
The article deals with the issues of emotional and volitional stability, acting as the leading ones in the system of moral and psychological support for the activities of the internal affairs bodies of the Russian Federation. The purpose of the article was to analyze the features of emotional and volitional stability of police officers of the territorial bodies of the Ministry of Internal Affairs of Russia and cadets of the educational organization of the Ministry of Internal Affairs of Russia. The sample is represented by two groups of 119 people, including police officers, 65 people, cadets of the educational organization of the Ministry of Internal Affairs of Russia - 54 people. The research methods were presented by the diagnostic unit: the questionnaire for assessing neuropsychic stability "Prognosis-2" (V.Yu. Rybnikov); the test "Lifestyle Analysis" (Boston stress tolerance test), the Individual typological questionnaire L.N. Sobchik, The methodology of the study of the volitional organization of the personality of A.A.Khokhlov, The test questionnaire of A.V. Zverkov and E.V. Eidman "The study of volitional self-regulation". Research results. The presence of significantly significant differences (p≤0.05) between the groups was established, indicating a higher level of neuropsychic stability, stress resistance and emotional-volitional regulation of police officers, which is determined by age characteristics and character accentuations. The normative indicators in both groups were not exceeded, which generally reflects the quality of professional psychological selection and the stability of the personality of police officers. В статье рассматриваются вопросы эмоционально-волевой устойчивости, выступающие в качестве ведущих в системе морально-психологического обеспечения деятельности органов внутренних дел Российской Федерации. Цель исследования состояла в анализе особенностей эмоционально-волевой устойчивости сотрудников полиции территориальных органов МВД России и курсантов образовательной организации МВД России. Выборка представлена двумя группами в количестве 119 человек, из них сотрудников полиции - 65 человек, курсантов образовательной организации МВД России - 54 человека. Методики исследования были представлены диагностическим блоком: анкета оценки нервно-психической устойчивости «Прогноз-2» (В.Ю. Рыбников); тест «Анализ стиля жизни» (Бостонский тест на стрессоустойчивость); «Индивидуально-типологический опросник» Л.Н. Собчик; «Методика исследования волевой организации личности» А.А. Хохлова; тест-опросник А.В. Зверькова и Е.В. Эйдмана «Исследование волевой саморегуляции». Результаты исследования показали наличие достоверно значимых различий (p≤0,05) между группами, свидетельствующих о более высоком уровне нервно-психической устойчивости, стрессоустойчивости и эмоционально-волевой регуляции у сотрудников полиции, что определяется возрастными характеристиками и акцентуациями характера. Нормативные показатели в обеих группах не превышены, что в целом отражает качество профессионального психологического отбора и стабильность личности сотрудников полиции.